2016
DOI: 10.1038/srep39730
|View full text |Cite
|
Sign up to set email alerts
|

The DE and FG loops of the HPV major capsid protein contribute to the epitopes of vaccine-induced cross-neutralising antibodies

Abstract: The human papillomavirus (HPV) vaccines consist of major capsid protein (L1) virus-like particles (VLP) and are highly efficacious against the development of cervical cancer precursors attributable to oncogenic genotypes, HPV16 and HPV18. A degree of vaccine-induced cross-protection has also been demonstrated against genetically-related genotypes in the Alpha-7 (HPV18-like) and Alpha-9 (HPV16-like) species groups which is coincident with the detection of L1 cross-neutralising antibodies. In this study the L1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…A study of B cell clones suggested that the specificity of antibodies elicited by vaccination, while overlapping with those derived from natural infection in some cases, were largely distinct in their specificity [23]. In addition, cross-reactive HPV31 antibodies elicited by the HPV vaccines appear to target antigenic domains distinct from those targeted by type-specific HPV31 antibodies [24]. Vaccine efficacy [2] and impact surveillance [5] studies suggest that vaccine effectiveness against HPV31 and HPV45 genotypes is significant, despite having relatively lower immunity against these genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…A study of B cell clones suggested that the specificity of antibodies elicited by vaccination, while overlapping with those derived from natural infection in some cases, were largely distinct in their specificity [23]. In addition, cross-reactive HPV31 antibodies elicited by the HPV vaccines appear to target antigenic domains distinct from those targeted by type-specific HPV31 antibodies [24]. Vaccine efficacy [2] and impact surveillance [5] studies suggest that vaccine effectiveness against HPV31 and HPV45 genotypes is significant, despite having relatively lower immunity against these genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The regions recognized by these mAbs were relatively conserved. Structure analysis on α9‐HPV VLPs indicates that L1 domains recognized by cross‐neutralizing antibodies comprise residues within DE and FG loops, 42 which were mostly surface exposed. We speculate that the cross‐neutralizing antibodies induced by sequential immunization with L1VLPs were possibly against these surface conserved regions, but the immunogenicity of these regions was very weak, and responses against them will require many heterologous boosts to be enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…have shown that in human immune response, antibodies bind to regions DE, EF, FG and H-I loop, making these regions of a high interest for HPV VLP recognition [ 40 ]. Moreover, DE and FG loops interact with the proline-rich regions of the L2 whereas a cysteine residue within the EF loop is crucial for the formation of inter-capsomeric L1-L1 disulphide bonds [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest, fine-mapping of the epitope footprint showed that the five non-synonymous changes of amino acids residues, including the ATC insertion and GAT deletion, are localized in the H2 and H4 helices and H-I and B-C loop regions T389P amino acid substitution is located in the H-1 loop, identified as an immunogenetic region of L1 capsid and believed to contribute towards cross-neutralising antibody [ 41 ]. M424I and M430I amino acid substitutions are located in the H4 helice whereas the Ser insertion is located in the H2 helice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation